2015
DOI: 10.1139/cjfas-2014-0394
|View full text |Cite
|
Sign up to set email alerts
|

Production rates of walleye and their relationship to exploitation in Escanaba Lake, Wisconsin, 1965–2009

Abstract: Understanding variability in fish production, biomass, production/biomass (P/B) ratios, and their relationship to exploitation is central to fisheries sustainability. At Escanaba Lake, Wisconsin, USA, data from a compulsory creel census were combined with survey data on fish populations to test for empirical relationships between annual production and exploitation rates of walleye (Sander vitreus). Empirical estimates of walleye production were relatively high and temporally variable in Escanaba Lake. Annual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(52 citation statements)
references
References 70 publications
2
50
0
Order By: Relevance
“…(), Rypel et al. (), and Tsehaye et al. (), which focus on target exploitation reference points, may suggest that the total allowable catch and limit reference point for CTWI Walleyes be lowered to decrease overall exploitation and compensate for long‐term declines in natural recruitment and productivity (Hansen et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(), Rypel et al. (), and Tsehaye et al. (), which focus on target exploitation reference points, may suggest that the total allowable catch and limit reference point for CTWI Walleyes be lowered to decrease overall exploitation and compensate for long‐term declines in natural recruitment and productivity (Hansen et al.…”
Section: Discussionmentioning
confidence: 99%
“…Rypel et al. () also suggested that exploitation rates >20% led to the harvest of all Walleye annual surplus production in Escanaba Lake, Wisconsin (the most productive Walleye lake in the CTWI; Rypel et al., in press), and Tsehaye et al. () showed that exploitation rates >20% on a simulated regional CTWI Walleye population reduced adult density to <7.4 fish/ha using a hierarchical Bayesian statistical catch‐at‐age model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Rypel et al. ). Thus, studies of production rates and biomass represent a natural conceptual bridge between these two, often‐segregated scientific fields.…”
Section: Introductionmentioning
confidence: 98%
“…Annual population estimates were converted to age-specific population values by 232 estimating the proportion of the population in different age classes (Rypel et al 2015). Annual production statistics for cisco in Trout Lake were highly variable over We found that production of cisco in Trout Lake exhibited considerable decline 333 until 2011.…”
mentioning
confidence: 90%